The analysis of the somatic phraseological unit of English and Karakalpak language - Nurillaev, Khamza Kudaybergenovich; Jumamuratova, Mukhabbat Azatbayevna (Science and Education, 2023)
This article discusses about the analysis of the somatic phraseological unit of English and Karakalpak languages. There given examples in both languages. The phraseology related to the terms of human body parts has a certain meaning. At the same time, they are also different in relation to word groups. Among them, phraseologisms with somatisms form a certain group.